Effects of social support on the association between precollege sexual assault and college-onset victimization. Issue 6 (18th August 2018) - Hawn, Sage E.; Lind, Mackenzie J.; Conley, Abigail; Overstreet, Cassie M.; Kendler, Kenneth S.; Dick, Danielle M.; Amstadter, Ananda B.
ABSTRACT: Objective : This study examined the moderating and mediating effects of perceived social support on the association between precollege sexual assault (SA) and college-onset SA.Participants : A representative sample of 6, 132 undergraduates.Methods : The PLUM procedure in SPSS was used to test the moderation model, with individual regressions conducted in a hierarchical fashion. A weighted least squared mean and variance adjusted (WLSMV) mediation model was used to examine the mediating effect of social support.Results : Precollege SA significantly predicted college-onset SA. Social support significantly mediated the relation between precollege SA and college-onset SA. Social support was not a significant moderator of this relationship.Conclusions : Given the high prevalence of SA among college populations, as well as the high rates of SA revictimization, identification of factors that may be related to repeated SA (eg, low social support) within this population are essential and may inform intervention, policy, and university student services.